Cardiomyopathy in Children: Classification and Diagnosis. Issue 1 (2nd July 2019) - Lipshultz, Steven E.; Law, Yuk M.; Asante-Korang, Alfred; Austin, Eric D.; Dipchand, Anne I.; Everitt, Melanie D.; Hsu, Daphne T.; Lin, Kimberly Y.; Price, Jack F.; Wilkinson, James D.; Colan, Steven D.
Abstract : In this scientific statement from the American Heart Association, experts in the field of cardiomyopathy (heart muscle disease) in children address 2 issues: the most current understanding of the causes of cardiomyopathy in children and the optimal approaches to diagnosis cardiomyopathy in children. Cardiomyopathies result in some of the worst pediatric cardiology outcomes; nearly 40% of children who present with symptomatic cardiomyopathy undergo a heart transplantation or die within the first 2 years after diagnosis. The percentage of children with cardiomyopathy who underwent a heart transplantation has not declined over the past 10 years, and cardiomyopathy remains the leading cause of transplantation for children >1 year of age. Studies from the National Heart, Lung, and Blood Institute–funded Pediatric Cardiomyopathy Registry have shown that causes are established in very few children with cardiomyopathy, yet genetic causes are likely to be present in most. The incidence of pediatric cardiomyopathy is ≈1 per 100 000 children. This is comparable to the incidence of such childhood cancers as lymphoma, Wilms tumor, and neuroblastoma. However, the published research and scientific conferences focused on pediatric cardiomyopathy are sparcer than for those cancers. The aim of the statement is to focus on the diagnosis and classification of cardiomyopathy. We anticipate that this report will help shape the future research priorities in this set of diseases to achieve earlier diagnosis, improved clinical outcomes, and better quality of life for these children and their families.